EFFECTIVITY OF TWO BLEACHING AGENT OF 10% CARBAMIDE PEROXIDE WITH AND WITHOUT POTASSIUM NITRATE-FLUORIDE (CLINICAL STUDY) - Ayus Lusiyanti; Munyati Usman; Safrida Hoesin (Faculty of Dentistry, Universitas Indonesia, 2015)
Tooth bleaching has become a popular treatment for esthetic improvement in dentistry. There are several 10% carbamide peroxide bleaching agents that are available in Indonesia which contained potassium nitrate-fluoride or without potassium nitrate-fluoride. However, there was no clinical report about these products in Indonesia. This study was conducted to compare the effectiveness of two bleaching and sensitivity of tooth and gingiva. Sixty-four participants were divided into 2 groups. The first group was treated with bleaching agent that contained potassium nitrate-fluoride (Opalescence PF, Ultradent). Bleaching treatment was done for 6-8 hours per night over a 2 week-period. Evaluations were performed at the baseline and at 3, 7, 14 day afterwards. Color change was measured using a value-ordered Vita classic shade guide; tooth and gingival sensitivity were examine using Electric Pulp Tester, Gingival Index and patient log. The results showed that there were no statistical differences in degree of color change between the two products. The mean color change after 2 weeks was 7-8 tabs lighter than baseline. Also there was no statistical difference in tooth and gingival sensitivity between the products. It can be concluded that 10% carbamide peroxide containing potassium nitrate-fluoride has the same effectiveness compared to other agent without potassium nitrate-fluoride for tooth color change and tooth and gingival sensitivity.